PENGARUH HARGA, FASILITAS, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Roy Adam Soekarno; Rahayu Triastity; Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance of the effect of price, facilities, service quality on customer satisfaction Grand Laguna Hotel & Villa Surakarta. This study uses survey methods, the type of data used are qualitative and quantitative data, the source of the data used are primary data and secondary data. The total population in this study was 400 people. In this study, because the population is more than 100, the sampling technique is accidental sampling, which is accidental sampling. Data collection techniques in this study used a questionnaire. Data analysis techniques used, Descriptive Analysis, Classic Assumption Test, Multiple Linear Regression Analysis, t Test, F Test and Determination Coefficient Test (R2). The results of this study concluded that the price has a significant effect on customer satisfaction Grand Laguna Hotel & Villa Surakarta. Facilities have a significant effect on customer satisfaction Grand Laguna Hotel & Villa Surakarta. Quality of service does not significantly influence consumer satisfaction Grand Laguna Hotel & Villa Surakarta.